Morphogenesis of bullet-shaped rabies virus particles requires a functional interplay between the viral matrix protein and ESCRT-I component TSG101 - Itakura, Yukari; Tabata, Koshiro; Saito, Takeshi; Intaruck, Kittiya; Kawaguchi, Nijiho; Kishimoto, Mai; Torii, Shiho; Kobayashi, Shintaro; Ito, Naoto; Harada, Michiko; Inoue, Satoshi; Maeda, Ken; et al. (bioRxiv, 2022)
Viral protein assembly and virion budding are tightly regulated to enable the proper formation of progeny virions. At this late stage in the virus life cycle, some enveloped viruses take advantage of the host ESCRT (endosomal sorting complex required for transport) machinery, which contributes to the physiological functions of membrane modulation and abscission. Bullet-shaped viral particles are unique morphological characteristics of rhabdoviruses; however, the involvement of host factors in rhabdovirus infection, and specifically the molecular mechanisms underlying virion formation are not fully understood. In the present study, we used a siRNA screening approach and found that the ESCRT-I component TSG101 contributes to the propagation of rabies virus (RABV). We demonstrated that the matrix protein (M) of RABV interacts with TSG101 via the late-domain containing the PY and YL motifs, which are conserved in various viral proteins. Loss of the YL motif in the RABV M or the downregulation of host TSG101 expression resulted in the intracellular aggregation of viral proteins and abnormal virus particle formation, indicating a defect in the RABV assembly and budding processes. These results indicate that the interaction of the RABV M and TSG101 is pivotal for not only the efficient budding of progeny RABV from infected cells but also for the bullet-shaped virion morphology. Enveloped-viruses bud from cells with the host lipid bilayer. Generally, the membrane modulation and abscission are mediated by host ESCRT (endosomal sorting complex required for transport) complexes. Some enveloped-viruses utilize their late (L)-domain to interact with ESCRTs, which promotes viral budding. Rhabdoviruses form characteristic bullet-shaped enveloped-virions, but the underlying molecular mechanisms involved remain elusive. Herein, we showed that TSG101, one of ESCRT components, supports rabies virus (RABV) budding and proliferation. TSG101 interacted with RABV matrix protein via L-domain, and the absence of this interaction resulted in intracellular virion accumulation and distortion of the morphology of progeny virions. Our study reveals that virion formation of RABV is highly regulated by TSG101 and the virus matrix protein.